Assessment of Accuracy of Rotator Cuff Tears on Shoulder Ultrasound with Respect to Magnetic Resonance Imaging - K S Vedaraju; Reddy, Basam Pavani (Asian Journal of Medical Radiological Research, 2022)
Background: The aim of the study is to assess the accuracy of ultrasound for diagnosis of rotator cuff tears with respect to magnetic resonance imaging, To identify partial thickness rotator cuff tears, full thickness rotator cuff tears and tendinopathic changes; and to evaluate the sensitivity and specificity of US in diagnosing them with respect to magnetic resonance imaging. Subjects and Methods: It is a prospective study conducted at the department of Radiodiagnosis in Narayana Medical College and Hospital, Nellore. A total of 30 patients who were suspected of having rotator cuff tear or tendinosis and planning to undergo MRI of shoulder were included in this study. Shoulder ultrasound was performed either before or after the MRI scan on same day. Findings of ultrasound were compared and correlated with findings of MRI. Results: Sensitivity (SN), specificity (SP), positive predictive value (PPV), negative predictive value (NPV), and accuracy for diagnosis of rotator cuff tear was 93%, 73%, 77%, 91%, and 83%, respectively. Conclusion: (SN) Sensitivity for diagnosis of rotator cuff tear was good and had a higher (NPV) negative predictive value. Consequently, operator of ultrasound even though having a short tenure of experience for performing ultrasound of shoulder had good sensitivity in diagnosing tears; and able to eliminate them with sureness.